If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -12 = 2x + 3 Reorder the terms: -12 + -3x = 2x + 3 Reorder the terms: -12 + -3x = 3 + 2x Solving -12 + -3x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + -3x + -2x = 3 + 2x + -2x Combine like terms: -3x + -2x = -5x -12 + -5x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + -5x = 3 + 0 -12 + -5x = 3 Add '12' to each side of the equation. -12 + 12 + -5x = 3 + 12 Combine like terms: -12 + 12 = 0 0 + -5x = 3 + 12 -5x = 3 + 12 Combine like terms: 3 + 12 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| x+1+8=10 | | 4(8+x)=6(x+3) | | x+10=-3 | | 9a^2-5= | | 13x+1+18=23 | | 3x^2+26x+16=0 | | 8c-4=20-4 | | 8c-4=20-40c | | -3x+3(2x-5)=-4-8x | | 10u^5+45u^4+45u^3=0 | | 8(x-5)=2(x+4) | | 3-5x=2x-1 | | 12x-3=15x-4 | | -2(x-2)+5(x+2)=17 | | 2v^2+15v+29(u+2)=0 | | 4(x+2)+3(x-1)=10 | | 12*s^3+19*s^2+8*s+1=0 | | 4(x-2)-3=-12 | | 3(x+1)+4=12 | | -10=-8+x/4 | | 7n+12=13n-6 | | 6+x/4=3 | | 2x+1=3-6x | | 4p+6=5p-1 | | x/4+7=4 | | -22-x=5+6+9 | | 2(x+3)+3(x+1)=10 | | 5+2(x-8)=-4 | | 2u^3+7u^2-12u-42=0 | | 20x+3=2x-9 | | 3(x-4)+8=7 | | 5(x+2)+7=19-x |